Phemindole, a Synthetic Di-indole Derivative Maneuvers the Store Operated Calcium Entry (SOCE) to Induce Potent Anti-Carcinogenic Activity in Human Triple Negative Breast Cancer Cells - Chakraborty, Supriya; Ghosh, Swatilekha; Banerjee, Bhaswati; Santra, Abhishek; Adhikary, Arghya; Misra, Anup K.; Sen, Parimal C. (Frontiers in Pharmacology, 2016)
Triple-negative breast cancer (TNBC), is a specific subtype of epithelial breast tumours that are immuno-histochemically negative for the protein expression of the estrogen receptor (ER), the progesterone receptor (PR) and lack over expression/gene amplification of HER2. This subtype of breast cancers is highly metastatic, shows poor prognosis and hence represents an important clinical challenge to researchers worldwide. Thus alternative approaches of drug development for TNBC have gained utmost importance in the present times. Dietary indole and its derivatives have gained prominence as anti-cancer agents and new therapeutic approaches are being developed to target them against TNBC. But a major drawback with 3, 3’di Indolyl methane (DIM) is their poor bioavailability and high effective concentration against TNBC. However the Aryl methyl ring substituted analogs of DIM display interesting anti-cancer activity in breast cancer cells. In the current study we report the synthesis of a novel synthetic aryl methyl ring substituted analog of DIM, named as Phemindole as an effective anti-tumor agent against TNBC cells. Furthermore, we enumerated that Phemindole caused ROS mediated mitochondrial-dependent apoptosis in MDAMB-231 cells. Furthermore, Phemindole mediated Store Operated Calcium Entry (SOCE) retardation favored inactivation of STIM1 and henceforth activated ER stress to induce apoptosis in TNBC cells. Simultaneously, Phemindole was also found to restrict the in-vitro cell migration through its anti mitotic property and pFAK regulation. Studies extended to ex-ovo and in-vivo mice models further validated the efficacy of Phemindole. Thus our results cumulatively propose Phemindole as a new chemotherapeutic regime which might be effective to target the deadly aspects of the TNBC.